Impact of Financial Literacy and Attitude on Resource Allocation Actors' Locus of Control as a moderating variable in the Small and Medium Food Industry - Rizky, Dyah Puteri; Sirat, Abdul Hadi; Dharma, Putri Ekawati (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study's overarching goal is to learn more about how financial knowledge, financial attitude, and locus of control all interact to influence financial management behaviour. Forty SME proprietors from Ternate (mostly Ternate Tengah and Ternate Selatan) make up the study's sample. Purposeful sampling was used to choose the sample. In this work, SEM-PLS was used to check for validity of hypotheses. Based on the data, it appears that Financial Knowledge does not significantly influence Financial Management Actions. That Locus of Control does not play a mediating role in the connection between financial knowledge and management behaviour is another implication of this research. However, Financial Attitude significantly and positively affects Financial Management Actions. The subsequent studies showed that the relationship between financial attitude and financial management behaviour was partially mediated by locus of control.